Memória: caminhos percorridos da minha história de vida na educação infantil à vida acadêmica - MORAES, Eugênia Patrícia Lobato (2024)
This work aims to report on my life trajectory, from early childhood education to my academic training, where I portray this trajectory with great satisfaction and joy. Because, through studies, I was able to expand my knowledge and acquire new ones. It's having a chance to become a professional who is concerned with education from childhood to adult life, because we know the reality of many people who do not have the encouragement of family members to study. So, I had the joy of having a family that encouraged me to study, and if today many students do not have the incentive at home, they will be able to find it in the classroom, when we, who will be future teachers with our training, will help this student to understand that without education we can hardly get anywhere, it is the basis of a good society. These opportunities that were given to me, in memory, I report as a way of demonstrating and encouraging education.